Judaism and Health: Reflections on an Emerging Scholarly Field - Levin, Jeffrey S. (Journal of religion and health, 2011)
This paper surveys the field of Judaism and health. The authors trace the history of discourse on health and healing within Judaism, from the biblical and rabbinic eras to contemporary research and writing on Jewish bioethics, pastoral care, communal services, and aging, including congregational and community programming related to health and illness and the emergence of the Jewish healing movement. The work of the Kalsman Institute on Judaism and Health is described, focusing on efforts to unite these various threads into a scholarly field emphasizing basic and applied research on the instrumental functions of Jewish religious life for health and well-being.